A Rapid Approach To Web Application Security - Schmit, Victor (My University, 2022)
After using and developing a web application tool at a company, it is now time for this tool to be productised and made available for use to external customers. Initially, as this was the company’s R&D internal tool, the security aspect never really was part of the coding process or the design. It is essential to, now, secure it before being able to release it to external servers and expose it to real threats. The work will focus on all the diferent aspects needed to start, apply and maintain a high level security in a web application such as the company’s web application. The work will go through processes such as vulnerability assessment, working as a team to fnd potential vulnerabilities and the best mechanisms to implement this security. To achieve this, we will make research as well as using the company’s internal security process requirements for security before productisation. The outcome of this work will help future web application security expert securing their own web application.
Keywords: Cybersecurity, Web Application Security, Completely Unsecure, Development